Class III malocclusion: missense mutations in DUSP6 gene - Nowrin, Shifat A.; Basri, Rehana; Alam, Mohammad Khursheed; Jaafar, Saidi; Mokhtar@Makhtar, Khairani Idah (Association Support to Oral Health Research, 2019)
Objective: To determine the DUSP6 gene mutation in three generations of Malaysian Malay subjects having Class III malocclusion. Material and Methods: Genetic analyses of DUSP6 gene were carried out in 30 subjects by selecting three individuals representing three generations, respectively, from ten Malaysian Malay families having Class III malocclusion and 30 healthy controls. They were submitted Clinical Evaluation to clinical examination, lateral cephalometric radiographs, dental casts, and/ or facial and intra-oral photographs. Buccal cell was taken from each participant of Class III malocclusion and control groups. DNA extractions from buccal cell were carried out using Gentra puregene buccal cell kit. Bio Edit Sequence Alignment Editor software was used to see the sequencing result. Results: A heterozygous missense mutation c.1094C>T (p. Thr 365 Ile) was identified in DUSP6 gene in three members of one family with Class III malocclusion, whereas no mutation was found in the control group. Conclusion: Current study successfully identified a missense mutation in DUSP6 gene among one Malaysian Malay family affected by Class III malocclusion. The outcome of this study broadened the mutation spectrum of Class III malocclusion and the importance of DUSP6 gene in skeletal functions.